Building Digital Communication Effectiveness in Organizations - Harjono Padmono Putro (Journal Of Data Science, 2023)
In facing this digital era, organizations are faced with the challenge of understanding and fully utilizing the potential of digital communications in order to achieve optimal effectiveness. Digital communication includes a variety of tools, such as online collaboration platforms, email, social media, and other technology-based applications. The success of an organization not only depends on the adoption of this technology, but also on the extent to which the organization is able to manage and build the effectiveness of communication through these digital media. Therefore, this research aims to establish the effectiveness of digital communication in an organization. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of digital communication in organizations has a positive impact on operational efficiency and productivity. Respondents highlighted that the use of digital communication tools, such as email and collaborative platforms, overcomes distance and time constraints, speeds up the exchange of information, and facilitates faster decision making. Employee engagement also increases through interactive communication channels, creating a more open and collaborative work environment. Despite this, challenges related to technological inadequacy and digital security issues remain major concerns that require strategic action in optimizing the benefits of digital communications within organizations.